Application of population genetic analysis of linked, mapped microsatellites to the identification of loci under selection for disease resistance - Park, S.D.E.; Adomefa, K.; Dao, B.; Hanotte, Olivier H.; Kemp, Stephen J.; Sow, R.S.; Teale, A.J.; Bradley, D.G. (1999)
We have sought to test the possibility of detecting regions of the genome under selection through effects on variation at linked neutral genetic markers. Particularly, we investigated three genomic regions identified by mapping in a cross-bred pedigree as harbouring QTL for trypanosomiasis tolerance. Population genetic analysis is used with mapped microsatellites to try to infer selection for trypanotolerance in West African cattle populations.